Screening for Genetic Mutations for the Early Diagnosis of Common Variable Immunodeficiency in Children With Refractory Immune Thrombocytopenia: A Retrospective Data Analysis From a Tertiary Children's Center - Ma, Jingyao; Fu, Lingling; Gu, Hao; Chen, Zhenping; Zhang, Jialu; Zhao, Shasha; Zhu, Xiaojing; Liu, Huiqing; Wu, Runhui (Frontiers in Pediatrics, 2020)
Aim: This study aimed to identify common variable immunodeficiency (CVID) by high-throughput next-generation sequencing (NGS) in children with refractory immune thrombocytopenia (RITP) to facilitate early diagnosis. Methods: CVID-related genetic mutations were explored in patients with RITP during 2016–2019. They were tested consecutively through NGS by the ITP team of the tertiary children hospital in China. An evaluation system was devised based on the phenotype, genetic rule, and serum immunoglobulins (Igs) of all patients with RITP. . The patients were divided into highly suspicious, suspicious, and negative groups using the evaluation system. Results: Among 176 patients with RITP, 16 (9.1%) harbored CVID-related genetic mutations: 8 (4.5%) were highly suspicious of CVIDs. Five had mutations in tumor necrosis factor receptor superfamily 13B (TNFRSF13B), one in lipopolysaccharide responsive beige-like anchor protein (LRBA), one in nuclear factor kappa-B2 (NF-κB2), and one in caspase recruitment domain11 (CARD11). Others were classified into the suspicious group because the clinical phenotype and pedigree were suggestive, yet insufficient, for diagnosis. Repeated infection existed in all patients. Two had an allergic disease. Positive autoimmune serologies were noted in 62.5%. Five had a definite positive family history. The median serum immunoglobulin (Ig)A, IgG, and IgM levels were 0.3875 g/L, 6.14 g/L, and 0.522 g/L, respectively. Nearly 85.7% of patients had insufficient serum IgA levels, while 37.5% had low IgG and IgM levels. Conclusions: High-throughput NGS and a thorough review of the medical history are beneficial for the early diagnosis of patients without any significant clinical characteristics, distinguishing them from those with primary pediatric ITP. The cases suspicious of CVID need further investigation and follow-up to avoid deterioration.